Interactive Media Development With Genially Application Materials Build Curved Side Space For Elementary School Students - Marvira Delvi; Jesi Alexander Alim; Mahmud Alpusari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study is a Research and Development (RD). This study was developed by using development models with three phases: the preliminary analysis phase, the development phase or manufacture (Prototyping Phase) and the assessment phase. The product developed in this study was an interactive media product with the genial application of curved side room building materials for elementary school students that have valid and practical criteria so that this interactive media product can be used by teachers and students. Moreover, the interactive media product can be an alternative to the learning process. Students were positively more enthusiastic in learning because the use of interactive media provided learning that was different from the usual learning, and developing interactive media with the application genially material builds curved side rooms can create the teaching and learning process more interesting. The aim of this study is to develop an interactive media development product with the application of genially valid and practical curved side building materials. The interactive media product was validated by three experts: material experts, media experts, and linguists. Meanwhile, the practicality of interactive media products was seen from the questionnaire of teacher responses to interactive media products and the practicality of students given by researchers during the trial was limited to small groups. Data collection techniques carried out by researchers were observation, interviews, and questionnaires. Data processing was carried out in a quantitative and qualitative.